Executive power [large type] - Andrews, Brian, 1973-; Wilson, Jeffrey, 1963- (Random House Large Print Publishing, 2025)
An international incident may fracture the Ryan family in the latest entry in this #1 New York Times bestselling series. Even in a family of strong individualists like the Ryans, Kyle has stood out as a lone wolf. For years he's gone his own way, joining the DIA rather than the CIA, and disagreeing with his father's politics. Now he's missing in an African country on the brink of a coup. His last message to his handlers, "We're on the wrong side of history." His father, the President of the United States, is about to discover which is more important to him: the interests of his country or the life of his son?